2003
DOI: 10.1108/02683940310494395
|View full text |Cite
|
Sign up to set email alerts
|

The use of mental imagery in the simulated employment interview situation

Abstract: In this study, interviewees in the training group were instructed to use mental imagery techniques in a simulated employment interview. Results indicated that the subjects who used mental imagery had higher performance in the interview and lower perceived stress than the subjects who did not use mental imagery. Mental imagery did not have a significant effect upon perceptions of self-efficacy. Mental imagery ability had a positive effect on perceived usefulness of mental imagery while controllability and vivid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 57 publications
0
21
1
Order By: Relevance
“…Results showed that participants who engaged in a simulation designed to control the stressful event reported more positive affect, greater intentions to accept the reality of the problem and, importantly, reported using more active, problem-focused coping strategies relative to control participants. Knudstrup, Segrest, and Hurley (2003) found that mentally simulating a job prior to an actual interview led to better performance compared to the control condition as rated by 202 CRISP ET AL.…”
Section: Imagery Intention and Behaviourmentioning
confidence: 96%
“…Results showed that participants who engaged in a simulation designed to control the stressful event reported more positive affect, greater intentions to accept the reality of the problem and, importantly, reported using more active, problem-focused coping strategies relative to control participants. Knudstrup, Segrest, and Hurley (2003) found that mentally simulating a job prior to an actual interview led to better performance compared to the control condition as rated by 202 CRISP ET AL.…”
Section: Imagery Intention and Behaviourmentioning
confidence: 96%
“…Because much of a job interview is unscripted, student on the autism spectrum may have to practice a variety of scenarios in reference to how to introduce themselves, making small talk, whether or not to shake someone's hand, and where to sit. Employment interviewing training programs have been shown to improve interview performance with neurotypical college students (Knudstrup et al 2003) The issue of whether and/or when the student should disclose their disability to a prospective employer can be complicated. Past research has shown that knowledge of a disability is a deterrent to granting an interview by employers (Peason et al 2003).…”
Section: Vocational Issuesmentioning
confidence: 99%
“…Are these intentions and tendencies translated into actual behavior? We know from the broader literature on mental simulation that such strategies can have a direct impact on actual behavior, ranging from interview performance (Knudstrup, Segrest & Hurley, 2003) to academic study (Rivkin & Taylor, 1999) to sporting performance (Feltz & Landers, 1983). There are therefore good reasons to expect imagined contact to result in more positive behaviors directed to the outgroup.…”
Section: Non-verbal Behaviormentioning
confidence: 99%